Modelo de localização de biodigestor com ênfase em cluster de parceria estratégica para geração de bioenergia - Jesus, Rômulo Henrique Gomes de (2021)
Bioenergy is a renewable energy obtained from biomass and the main benefits are the reduction of greenhouse gas emissions and waste elimination. A common problem in the feasibility analysis for bioenergy production is the location of the biodigester due to the availability and spatial positioning of the biomass. Faced with this problem, this research aims to answer the following question: How to locate a biodigester in agribusiness with a view to forming clusters of strategic partnerships for the production of bioenergy? Therefore, the objective of this dissertation is to propose a model for the location of anaerobic digester in the agribusiness by creating clusters of strategic partnerships for the generation of bioenergy. To this end, a systematic literature review was carried out and a set of biodigester location models were identified as the main methods used for the decision to locate the biodigester: multicriteria decision analysis, heuristics, mathematical programming and Geographic Information System (GIS) . The identified studies have no emphasis on the formation of a cluster to determine the location of the biodigester, therefore, in order to cover the literature gap, a model is proposed that encompasses cluster formation and identification of the location of the biodigester in a strategic partnership environment for the generation of bioenergy. The proposed model has application of multicriteria technique, use of GIS and agglomerative hierarchical algorithm for the formation of clusters. Also, it has features that allow it to be applied to large and small regions, allowing stakeholders to integrate variables that can be minimized or maximized into the model, thus, this feature makes the model flexible to users' needs. Through the model, stages of analysis are established that allow, from a quantitative and qualitative perspective, to preliminarily identify the possibility of creating a strategic partnership and the location of a biodigester. Finally, the model is applied in the context of a cooperative that has properties (farms) with an interest in producing bioenergy in clusters. Thus, a feasibility map is proposed for a region in the state of Paraná (Brazil) to validate the formation of clusters. These, if implemented, can enable more sustainable and competitive productive systems, creation of new jobs, preservation of the environment and reduction of production costs through the use of self-consumed energy.